Biodegradable straws (Business Vision, 2020)
What is sought with the implementation of this project is to contribute to the reduction of a large percentage of pollution caused by disposable cigarettes, and a great way to do so is to replace these cigarettes, by biodegradable ones, which degrade in a more time short in comparison to the disposable ones, because they are elaborated based on the cocoa peel and the cheese whey that have a rapid decomposition and do not affect the medium. This research initially has an introduction that will give you a broader idea of the project, where the respective research was carried out under the quantitative paradigm, empirical analytical approach, descriptive type and the deductive method, these being the components of the methodology. It was applied as a method of data collection different encuetas, which gave us to know the necessary information for the elaboration of the product and the creation of the company, where it could be analyzed that if it is a viable, feasible product, and know the characteristics and customer tastes with respect to the product allowing segment the market.
Keywords: methodology; shell; biodegradable skinny